The Effect Of Organizational Culture, Employee Empowerment, Emotional Intelligence on Job Satisfaction Through Organizational Commitment at PT. Madusari Nusaperdana - Nurjanah, Nenden Indah; Hasanudin, Hasanudin (Yayasan Riset dan Pengembangan Intelektual, 2024)
The aim of this study to analyze and examine the factors influencing the organizational culture, employee empowerment and emotional intelligence on job satisfaction with organizational commitment as an intervening variable at PT. Madusari Nusaperdana. The study involves 130 employees from both general and personnel divisions, comprising the research population. The method of research is using the quantitative and regression analysis. The sampling technique used an purposive sampling. The data was analyzed with Partial Least Squares-Structural Equation Modeling (PLS-SEM). Based on the analysis, the research shows that the employee empowerment and emotional intelligence has a significant positive effect on job satisfaction, while organizational culture does not have a significant effect on job satisfaction at PT. Madusari Nusaperdana. The organizational commitment is able to mediate the influence of employee empowerment and emotional intelligence on job satisfaction, while the organizational commitment is unable to mediate the influence organizational culture on job satisfaction. The practical implications of this research are intended to guide decision-making and policy formulation regarding organizational culture, employee empowerment, emotional intelligence and job satisfaction within PT. Madusari Nusaperdana.